Current velocity shapes co‐existence patterns among invasive Dikerogammarus species. (22nd November 2016) - Borza, Péter; Huber, Thomas; Leitner, Patrick; Remund, Nadine; Graf, Wolfram
Summary: Facilitative interactions among co‐evolved representatives of the endemic Ponto‐Caspian fauna are regarded as a major factor of their invasion success. Nevertheless, the most renowned examples represent interactions between different trophic levels or functional groups, while ecologically similar species can be expected to show competition‐based niche partitioning. Here, we test for differences in the realized niche of three invasive Dikerogammarus species (Crustacea: Gammaridae) in their co‐occurring range. We sampled multiple habitats within sites distributed along the River Danube to test whether some environmental variables could reveal spatial niche differentiation among the three species of Dikerogammarus, and if so, to test a predictive model outside the zone of co‐occurrence. Spatial niche differentiation was present among the species, primarily determined by current velocity (and associated substrate preference), likely reflecting a stress tolerance–competitive ability trade‐off. Suspended matter concentration was also relevant, suggesting food resources (through filter feeding) might represent another important niche axis, somewhat loosening the terms of co‐existence between D. haemobaphes and the other two species. Environmental variables could effectively explain the absence of D. bispinosus in the Lower Danube, implying that the co‐existence of the three species is possible only along a sufficiently wide current velocity gradient, and the observed turnovers are the result of niche expansion in the absence of the stronger competitor. Hence, differences in invasion success may be attributed to a stress tolerance–competitive ability trade‐off. Our results suggest the advantage of D. villosus is attributable to its competitive dominance, allowing it to monopolize lentic and/or structured habitats, which represents a fortunate pre‐adaptation to anthropogenic alterations of aquatic ecosystems. The presence of D. villosus does not greatly affect the expansion of D. haemobaphes ; however, the exclusion of D. bispinosus from lentic habitats by D. villosus probably strongly limits its potential to spread by active dispersal.